Two new species of Palapedia Ng, 1993 (Crustacea, Decapoda, Brachyura,Xanthidae) from the Persian Gulf - Naderloo, Reza (Zootaxa, 2015)
Two new species of Palapedia Ng, 1993, are described based on material collected from Abu-Musa Island, Persian Gulf during the present study, from Bahrain by the 1937/38 Danish Expedition, and from the Saudi Arabian coast of the Persian Gulf by Michael Apel in 1992–1995. Palapedia persica n. sp. is distinguishable from its congeners by having distinctly large denticles on the upper margin of the palm and fingers of the chelae and anterior margin of the ambulatory dactyli, and by the markedly sickle-shaped dactylus of the ambulatory legs. Palapedia apeli n. sp. is similar to P. valentini Ng, 1993, and P. nitida (Stimpson, 1858), by having relatively smooth appendages.